Redescovering economic policy as a discipline: A note - Romagnoli, Gian Cesare (Journal of Economics Research and Policy Studies, 2025)
The reasons for the demise of economic policy as a value-laden normative theory, within the Frisch-Tinbergen-Theil approach, and those for its reappraisal are very important for academic research. They are critically analyzed in this note which discusses some arguments made in the last Nicola Acocella’s fully-fledged book Rediscovering Economic Policy as a Discipline. He defends the status of Economic Policy as a proper normative discipline of Economics aimed to the foundation, coordination and reach of government action claiming that the two vital critiques to the effectiveness of macroeconomic policy actions, i.e. the Arrow’s Impossibility Theorem and the Lucas Critique, may be overcome by a theory of economic policy in a strategic setting. So doing, though, he cuts across several important issues like the formation of economic expectations, the aggegation problem, the Public Choice hypothesis of self-interested policy-making, the necessity of microfoundations of macroeconomics taken for granted, the basic characteristics of the positive method based on empirical observation and analytical consistency, overall the hypotheses on which the economic policy models are based. Well, Acocella’s strategic setting approach is interesting but the two vital critiques and the other problems remain.